Comparative Study of Rheological Properties of Gels and Creams on Different Carrier Bases - U. V. Nogaeva; A. A. Naumova; A. G. Novinkov; E. V. Flisyuk; M. A. Burakova; A. N. Shikov; O. N. Abrosimova (Разработка и регистрация лекарственных средств)
Introduction. The study of rheological properties (dynamic and plastic viscosity, yield strength, the degree and presence of a thixotropic effect, the nature of the type of flow) are important for the development of soft dosage forms. These properties affect the stability of the dosage form during storage, its technological and consumer characteristics .Aim. Study of the main rheological parameters of the developed gels and creams on various carrier bases.Materials and methods. Meloxicam as active ingredient and excipients: sodium alginate, twin-80, propylene glycol, cremophor, glycerin, essential oils of lemon and orange, carbopol 980, polyethylene glycol-400 (PEG-400), viburnum bark, chamomile flowers, chlorhexidine bigluconate 20 %, menthol, sorbitol, corn oil, distilled monoglycerides (MHD), cetyl alcohol, coconut oil, salicylic acid, emulsion wax, preparation OS-20, triethanolamine (TEA), and euxil PE 9010 were used for the preparation of ex[eroimental samples. Three laboratory samples of soft formulations with the mass of 100 g each were prepared. The rheological properties of the samples were tested 24 hours after their preparation using Anton Paar DV-2P viscometer (Anton Paar GmbH, Austria), spindle L4. The structural and mechanical properties of the samples were tested using a device designed at the St. Petersburg State Chemical and Pharmaceutical University under thesupervision of Professor, Doctor of Pharmaceutical Sciences V. A. Vainshtein.Results and discussion. The greatest mechanical stability was observed for the sample No. 1 (gel based on alginate) and sample No. 3 (cream). The ascending and descending hysteresis loop curves indicates that the test samples have thixotropic properties. Samples No. 1 and 2 have upward and downward flow curves superimposed on each other.This phenomenon is typical for all gels and is their feature. The relaxation of the structure of an elastic-plastic material after the deformation caused by the introduction of a tester stock occurs according to the logarithmic law. At rest, when the tester stockis not introduced into the material, the structure of tested samples is intact and samples has a maximum density (static viscosity). The introduction of the tester stock into the sample results in plastic deformation and forced flow. The tension at the moment of tester stock introduction reflects the yield strength.Further, with the immersed tester devoce, a thixotropic recovery of the destroyed structural bonds occurs. Such a pattern in the dynamics of structure resistance is observed for structured (non-Newtonian) liquids.Conclusion. The rheological properties of three experimental soft formulations made on different carrier bases were investigated. The importance of rheological studies in the drug development of high e quality soft formulations was shown.